E-148 Flow divertor stenting for intracranial aneurysms in pediatric patients: case series and literature review. (23rd July 2022) - Feller, C; Porwal, M; Hedayat, H; Sacho, R
Abstract : Intracranial aneurysms (IAs) are rare in the pediatric population, and their treatment is often more difficult and complex than that of adults. 1 We present two pediatric patients with intracranial aneurysms that underwent Flow Diversion. Both showed significant improvement in pre-operative neurologic symptoms with almost complete resolution of the aneurysm. More research utilizing flow diversion in the pediatric population should take place to determine if this is a considerable alternative to typical embolization techniques. Disclosures: C. Feller: None. M. Porwal: None. H. Hedayat: None. R. Sacho: None.